2020
DOI: 10.3390/nu12123742
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dietary Glycemic Index, Glycemic Load and Carbohydrate with the Risk of Cervical Intraepithelial Neoplasia and Cervical Cancer: A Case-Control Study

Abstract: Background: The association of dietary glycemic index (GI) and glycemic load (GL) with the risk of cervical cancer has never been investigated. Thus, we aimed to find evidence of any association of GI and GL with the risk of cervical intraepithelial neoplasia (CIN) and cervical cancer. Methods: In this hospital-based case-control study, we included 1340 women (670 controls and 262, 187 and 221 patients with CIN1, CIN2/3, and cervical cancer, respectively) from the Korean human papillomavirus cohort study. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…Navarro-Meza et al reported that high levels of glucose in plasma and obesity could be risk cofactors in the development of precancerous lesion of cervix [42]. Similarly, in a Korean case-control study of 1340 cases (670 controls and 262, 187 and 221 patients with CIN1, CIN2/3, and cervical cancer, respectively), GL and GI is observed positively associated with increased risk of CIN1 but not with the risk of CIN2/3 and cervical cancer [43].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Navarro-Meza et al reported that high levels of glucose in plasma and obesity could be risk cofactors in the development of precancerous lesion of cervix [42]. Similarly, in a Korean case-control study of 1340 cases (670 controls and 262, 187 and 221 patients with CIN1, CIN2/3, and cervical cancer, respectively), GL and GI is observed positively associated with increased risk of CIN1 but not with the risk of CIN2/3 and cervical cancer [43].…”
Section: Introductionmentioning
confidence: 94%
“…HPV 16 and 18 are the main cancer-causing types, and the rest are HPV 31,33,35,45,52, and 58. The type and pattern of HPV infection varies by geography and economy [17]. In HPV positive cervical cancer, the expression of GLUT1 indicates a worse prognosis [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low-GI and an energy-restricted diet containing moderate amounts of carbohydrates may reduce body weight and control glucose and insulin metabolism (178). Those following the low-sugar and low-GI diet should consume large amounts of vegetables rich in fiber and phytonutrients (179), avoid the intake of carbohydrate-rich foods, such as bread, noodles, pasta, and starchy vegetables, as in the Western diet (180,181), and cakes, candy, biscuits, and sugar-sweetened beverages are forbidden (182). Turati et al (183) found that high-GL diets may have an adverse effect on blood glucose levels, insulin, and IGFs, resulting in an increased risk of PC.…”
Section: The Low-sugar Dietmentioning
confidence: 99%
“…Conclusively, GLUT1 is a promising diagnostic approach, wherein the glucose metabolism can potentially act as an intervention target in the treatment of cervical cancer. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%